Identification of an Arg-Gly-Asp (RGD) cell adhesion site in human immunodeficiency virus type 1 transactivation protein, tat (The Rockefeller University Press, 1990)
Tat, the transactivation factor of human immunodeficiency virus type 1 (HIV-1), contains the highly conserved tripeptide sequence Arg-Gly-Asp (RGD) that characterizes sites for integrin-mediated cell adhesion. The tat protein was assayed for cell attachment activity by measuring the adhesion of monocytic, T lymphocytic, and skeletal muscle-derived cell lines to tat-coated substratum. All cell lines tested bound to tat in a dose-dependent manner and the tat cell adhesion required the RGD sequence because tat mutants constructed to contain an RGE or KGE tripeptide sequence did not mediate efficient cell adhesion. The tat- mediated cell attachment also required divalent cations and an intact cytoskeleton. In addition, cell adhesion to tat was inhibited in the presence of an RGD-containing peptide GRGDSPK or an anti-tat mAb that recognizes the RGD epitope. These results strongly suggest that cells are bound to tat through an integrin. Interestingly, myoblast cells bound to tat remained round, whereas the same cells attached through an integrin for a matrix protein typically flatten and spread. The role of this RGD-dependent cellular adhesion of tat in HIV-1 infection remains to be determined.